Not So Ambitious? Indonesia’s Coal Dependence Amidst The Era of Energy Transition - Amira Hasna Febriyanti; Sayyid Al Murtadho; Yassriani Almattushyva (Global South Review, 2023)
Indonesia ratified the Paris Agreement to combat climate change and pledged to reduce its carbon emissions. This commitment, however, contrasts Indonesia's development plan under Joko Widodo's administration. His policy has enabled the development of additional power plants, hence perpetuating Indonesia's reliance on coal. Thus, it is essential to examine why Indonesia is still struggling to break free from its dependence on coal, despite its ambitious goal to tackle climate change. This paper will apply the Copenhagen School's securitisation theory to explore how security is defined and shapes Indonesia's energy transition process. Furthermore, this research will use distributive and procedural justice theory to examine the decision-making process and climate change policy implementation. In order to accomplish so, we will employ qualitative methods such as desk studies, which will comprise academic literature as well as government statements and regulations. This paper argues that Indonesia's energy transition is impeded by how other security issues are prioritised above climate change. In addition, the lack of justice principles in the climate policy formulation and implementation has contributed to Indonesia's reliance on coal. Since Indonesia is the world's largest coal exporter and one of the top ten global polluters, this study intends to contribute to identifying challenges in the transition to renewable energy.Keywords: Indonesia; coal dependence; energy transition; securitisation; distributive and procedural justice